INOVASI AKAD PEMBIAYAAN KARTU KREDIT SYARIAH - Abdul Sumarlin; Helmy Syamsuri; Abdul Rahman Ambo Masse Ambo Masse (Jurnal Teknologi Pendidikan Madrasah, 2024)
This research is entitled "Innovations in sharia credit card financing contracts", the aim of this research is to find out contract innovations and additional services in sharia credit card financing. The type of research used is descriptive or exploratory research, in this case it focuses on describing and explaining contract and service innovations. addition to sharia credit card financing, using a qualitative approach. Data sources come from official documents of Islamic financial institutions, academic publications. This research uses the library research method (library study) which means procedures for collecting information and data with the help of various references such as the Qur'an, books, articles, journals, theses, dissertations which are related to card financing agreements. credit. The results of the research show that the types of sharia credit card financing contracts based on the DSN-MUI are determined to be 3 (three) contracts, including the Kafalah, Qard, and Ijarah contracts, then implemented in sharia banking companies, there are 4 (four) contracts, namely the Kafalah, Qard, Ijarah, and sharf.